Landslide early warning based on improved tangential angle and displacement rate: A case study of the Leijiashan landslide in Shimen County, Hunan Province - Quanming CHEN; Weimin HUANG; Jiao LI (Zhongguo dizhi zaihai yu fangzhi xuebao)
To study landslide monitoring and early warning methods in Hunan Province，and to improve the success rate of early warning，the Leijiashan landslide in Shimen County is used as a representative case. Through a detailed site investigation, this paper describes the characteristics of the landslide and provides a comprehensive analysis of its failure mechanism. The results reveal that the unique landscape and loose soil structure are internal factors contributing to the occurrence of the landslide, while heavy rainfall and the engineering excavation are external factors. By utilizing the GNSS system，complete displacement-time curves are obtained, and the types and features of these curves are analyzed to identify the evolutionary characteristics of the landslide，which include three stages: initial deformation, constant deformation, and accelerated deformation. Therefore, the landslide is classified as a gradual change type. By using the tangent angle and deformation rate thresholds as important indicators for landslide early warning，an early warning criterion is established. It is integrated with the community-based disaster prevention and early warning information platform, providing direct evidence for relevant departments to carry out disaster prevention, reduction, and emergency response. Successful mitigation of the Leijiashan landslide validates the practicality of this monitoring and early warning method.